Green economic efficiency and influencing factors analysis of the Yangtze river economic belt in China - Jiani, WU (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
For a long time, China’s economic development ignore the constraints of resources and environmental costs but one-sided pursue GDP. In 2014, the State Council issued a document to develop the Yangtze River economic zone into a "green ecological corridor". The green development of the Yangtze River economic zone is of high-profile. This paper attempts to consider the resource and environmental factors into the economic growth, establish a reasonable evaluation of national and regional economic performance of the green economic efficiency indicators. It can be seen from the DEA estimates that the average green economic efficiency of the Yangtze River economic zone per year is more than 0.9. The Tobit panel model shows that there are differences in the factors affecting the green economic efficiency of different area. But overall, there is a "inverted U-type" relationship between green economic efficiency and per capita GDP, urbanization has a positive effect on green economic efficiency but not significant. Besides, foreign direct investment, structure factors, level of science and technology have a negative effect. According to the results of the inspection, this paper puts forward some policy suggestions on weighing the relationship between economic growth and environmental protection, taking a new road to industrialization and narrowing regional differences.